Removal of Pb(II) from Water Using Nanoscale SBA-15 - Ma, Yu-Qin; Zhai, Qing-Zhou; Yu, Hui; Yang, Mao-Jun (Asian Journal of Chemistry, 2011)
Nanoscale SBA-15 molecular sieve was synthesized by hydrothermal method. The prepared material was characterized by powder X-ray diffraction and scanning electron microscopy. The fibrous grains with a diameter of 333 ± 5 nm were obtained. The prepared materials were modified with mercaptoethanol, mercaptoacetic acid, respectively and mercapto-modified functionalized SBA-15 (MP-SBA-15) were obtained. SBA-15, mercaptoethanol modified SBA-15 and mercaptoacetic acid modified SBA-15 were used as adsorbents, respectively to adsorb the Pb2+ in water. The effects of acidity, time and temperature on the efficiency of adsorption were studied and the optimum adsorptive conditions were confirmed. The results showed that the adsorptive effect on Pb2+ by the SBA-15 modified by mercaptoacetic acid is better than those by SBA-15 and the SBA-15 modified by mercaptoethanol. Its greatest adsorptive ratio reached 98.49 % when the pH was 6, temperature was 30 ºC and adsorptive time was 50 min. Nitric acid, hydrochloric acid and acetic acid were used as desorbents and the effect of desorptive time on the efficiency of desorption was dicussed. The results showed that 0.1 mol/L of nitric acid has a better desorptive ratio than those of hydrochloric acid and acetic acid. Its greatest desorptive ratio reached 77.38 % when desorptive time was 50 min.